Diffusion characteristics and reinforcement effect of cement slurry on porous medium under dynamic water condition considering infiltration. (December 2022) - Du, Xueming; Liu, Chang; Wang, Chaojie; Fang, Hongyuan; Xue, Binghan; Gao, Xinlei; Han, Yahong
Highlights: The diffusion characteristic of cement-based grouting material flowing in soil media is studied. The water velocity, the concentration of cement, and the fractal dimension are considered. The physicochemical bonding mechanisms are studied. Abstract: Grouting methods are known to effectively remediate the groundwater inrush in tunnels with weak water-rich sand layers. However, the diffusion characteristic of cement slurry flowing in rock and soil media with flowing water is one of the many critical issues that still remain unsolved. The cement-based grouting material diffusion characteristics of water in rock, considering four grouting parameters of water-cement ratio, water flow speed and fractal dimension of particle mass, were researched through a series of experiments such as cement particle filtration, nuclear magnetic resonance and diffusion test. Then compressive strength, scanning electron microscope(SEM) and mercury intrusion porosimetry(MIP) were performed on consolidated specimens to examine physico-chemical bonding mechanisms characteristics. The results indicate that 1) The viscosity of the effluent at the test point varies with the increase of water discharge velocity with different water cement ratio. When the water cement ratio is low, the viscosity of effluent increases first and then decreases with the increase of water flow rate. For high water cement ratio, the viscosity of the same test point decreases with the increase of water velocity. 2) The porosity of the consolidation with a low water velocity is lower than that of the media with a high water velocity within 4 m of the injection site. However, when it exceeds 4 m, the porosity has the opposite trend. 3) In the range of 0.3 ∼ 0.4 m, the grouting pressure at middle and low velocity is higher than that of high velocity. Beyond this range, the trend is reversed. 4) When cement slurry flows in particles, its pressure attenuation law is not affected by the state of dynamic water and is only related to the fractal dimension of particles. Its pressure attenuation decreases sharply with the increase of distance, when cement slurry flows in the particle mass with higher fractal dimension. Nevertheless, the flow pressure of cement slurry decreases slowly with the increase of distance at low fractal dimension. 5) The compressive strength of the consolidated body of cement and sand decreases with the increase of water-cement ratio and distance. Microstructural changes in sand fabric indicate that cement grouting material modified the porous network of consolidated sand. The pores were filled and particles were bonded by hydration product of cement.